Molecular Mechanism of Epimedium Extract against Ischemic Stroke Based on Network Pharmacology and Experimental Validation. (27th October 2022) - Xu, Hongbei; You, Mingyao; Xiang, Xiang; Zhao, Jun; Yuan, Ping; Chu, Lan; Xie, Chenchen
Abstract : Ischemic stroke exhibits high morbidity, disability, and mortality, and treatments for ischemic stroke are limited despite intensive research. The potent neuroprotective benefits of Epimedium against ischemic stroke have gained lots of interest. Nevertheless, systematic research on the direct role and mechanisms of Epimedium in ischemic stroke is still lacking. Network pharmacology analysis coupled with experimental verification was utilized to systematically evaluate the potential pharmacological mechanism of Epimedium against ischemic stroke. The TCMSP database was used to mine the bioactive ingredients and Epimedium's targets. The DrugBank, OMIM, and GeneCards databases were employed to identify potential targets of ischemic stroke. GO and KEGG pathway analyses were also carried out. The interaction between active components and hub targets was confirmed via molecular docking. An experimental ischemic stroke model was used to evaluate the possible therapeutic mechanism of Epimedium. As a result, 23 bioactive compounds of Epimedium were selected, and 30 hub targets of Epimedium in its function against ischemic stroke were identified, and molecular docking results demonstrated good binding. The IL-17 signaling pathway was revealed as a potentially significant pathway, with the NF- κ B and MAPK/ERK signaling pathways being involved. Furthermore, in vivo experiments demonstrated that Epimedium treatment could improve neurological function and reduce infarct volume. Additionally, Epimedium reduced the activation of microglia and astrocytes in both the ischemic penumbra of the hippocampus and cerebral cortex following ischemic stroke. Western blot and RT–qPCR analyses demonstrated that Epimedium not only depressed the expression of IL-1 β, TNF- α, IL-6, and IL-4 but also inhibited the NF- κ B and MAPK/ERK signaling pathways. This study applied network pharmacology and in vivo experiment to explore possible mechanism of Epimedium's role against ischemic stroke, which provides insight into the treatment of ischemic stroke.